Penerapan Fungsi Dan Peran Al-Hisbah Dalam Pengawasan Di Baitul Maal Wa Tamwil - Muhammad Al ikhwan Bintarto; Luthfi Noor Mahmudi; Ferdin Okta Wardana (Universitas Muhammadiyah Surabaya, 2021)
AbstractSupervision is an important thing in an activity, the purpose of supervision is so that an activity is in accordance with the plan and does not deviate from the specified path, Islam has carried out long supervision at the time of the Prophet which was carried out by the hisbah institution or market supervisory agency, the principle or concept of al-hisbah in carrying out supervision is amar ma'ruf nahi munkar, this research uses a qualitative method with a literature study with data collection techniques using literature studies where data sources are taken and collected from books, journals, previous research or from websites which are then read and processed into material. research, and the result of this study is that if Islamic financial institutions can implement the concept of al-hisbah institution it will minimize violations of sharia and remain within the scope of Islamic law.Keywords: Al-hisbah, baitul maal wa tamwilAbstrakPengawasan merupakan suatu hal yang penting dalam suatu kegiatan, tujuan pengawasan adalah agar suatu kegiatan sesuai dengan rencana dan tidak menyimpang dari jalan yang telah ditentukan, Islam telah lama melakukan pengawasan pada zaman Rasulullah yang dilakukan oleh lembaga hisbah atau lembaga pengawas pasar, prinsip atau konsep al-hisbah dalam melakukan pengawasan adalah amar ma'ruf nahi munkar, penelitian ini menggunakan metode kualitatif dengan studi kepustakaan dengan teknik pengumpulan data menggunakan studi kepustakaan dimana sumber data diambil dan dikumpulkan dari buku, jurnal, penelitian sebelumnya atau dari website yang kemudian dibaca dan diolah menjadi bahan. penelitian ini, dan hasil dari penelitian ini adalah jika lembaga keuangan syariah dapat menerapkan konsep lembaga al-hisbah maka akan meminimalkan pelanggaran syariah dan tetap dalam lingkup hukum Islam.Kata kunci: Al-hisbah, baitul maal wa tamwil